Estimating the soil carbon sequestration potential of China's Grain for Green Project. Issue 11 (18th November 2014) - Shi, Shengwei; Han, Pengfei
Abstract The largest area of planted forest in the world has been established in China through implementation of key forestry projects in recent years. These projects have played an important role in sequestering CO2 from the atmosphere, which is considered to be a potential mitigation strategy for the effects of global climate change. However, carbon sequestration in soil (soil organic carbon, SOC) after afforestation or reforestation is not well understood, particularly for specific key forestry projects. In this study, the SOC change in the top 20 cm of soil for each type of restoration implemented under China's Grain for Green Project (GGP) was quantified by a meta‐analysis of data from published literature and direct field measurements. Soil carbon sequestration due to the GGP during 1999–2012 was estimated using data on the annual restoration area at provincial level and functions that relate SOC stock change to controlling factors (e.g., plantation age, forest zone, and type of forestation). Soil carbon sequestration of the GGP was estimated to be 156±108 Tg C (95% confidence interval) for current restoration areas prior to 2013, with a mean accumulation rate of 12±8 Tg C yr−1. The soil carbon sequestration potential of existing plantation zones is predicted to increase from 156±108 Tg C in 2013 to 383±188 Tg C in 2050 under the assumption that all plantation areas are well preserved. Plantations in northwestern, southern, and southwestern zones contributed nearly 80% of total soil carbon sequestration, while soil C sequestration in northeastern China was much more variable. Improved data sources, measurements of SOC in the organic layer, greater sampling depth, and better distribution of sampling sites among GGP regions will reduce the uncertainty of the estimates made by this study.